Pengembangan E-Modul Kontekstual Akuntansi Perbankan Syariah Kelas XI Berbasis Flip Pdf Professional - Lesta Denisa; Luqman Hakim (Jurnal Pendidikan Akuntansi (JPAK), 2021)
This research aims to develop teaching materials for Islamic banking accounting contextual e-module for class XI semester 1 with the help of professional flip pdf applications. The development of e-modules is based on the challenges of 21st century learning innovation, the absence of technology-integrated learning media so that online learning in the Covid-19 pandemic does not run effectively, and there is no learning media that contains basic competencies coherently. This research uses the Analysis, Design, Development, Implementation, Evaluation (ADDIE) model. Collecting research data using review sheets and validation sheets of experts as well as student response questionnaires. The subjects of this research trial were 10 students of SMK Negeri 2 Mojokerto. The results showed that the product was very feasible. Product eligibility is calculated based on the material feasibility average, graphic feasibility average, and language eligibility average. Student response to the product is very good and very feasible. Based on the results of the feasibility of the products of the experts and the student response tests, it shows that the product is very suitable for use as teaching materials in the 21st century era.